PENERAPAN MODEL PEMBELAJARAN DISCOVERY UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA PADA SISWA KELAS IV SD INPRES 2 KAYUMALUE NGAPA - Erwinda, Erwinda (JSTT, 2015)
The main problem of this research is the low of motivation and scientific learning outputs of year four students of Elementary School, SD Inpres 2 Kayumalue Ngapa. Base on this problem, the action classroom research is undertaken. The aim of this research is to implement the discovery learning model. The instruments used are lesson study plans, questioners, sheets of teacher and student’s activities, final test results. Allinstruments are used at two cycles which each cycle is held 3 times on teaching. At the first and second teaching described the application ofthe discovery learning model, then the last teaching is evaluation which done as the last action of the test.The result shows that learning used the discovery learning model can increase the student’s motivation on learning of science subject at year four elementary school, SD Inpres 2 Kayumalue Ngapa. The average of student motivation on cycle I is categorized medium whereas on cycle II is categorized high by using this learning model. The increasing of student’s learning output base on the completion achievement of pre-action of 25 students, only 9 students (36%) reached the completion.On cycle I, it reaches 15 students (60%) and on cycle II, reaches 23 students (92 %) gain this completion. This discovery model shows the average percentage of teacher’s activity completion on cycle I is 53% (adequate) and student’s activity is 51,25 % (adequate). On cycle II, teacher’s activity average is 91,6 % (excellent) and student’s activity average is 77,92% (good). The achievement of criterion of classical completion is influenced by being the motivation and optimal of teacher and student’sactivities during the learning on the process.